Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2014-2021 between programme countries - Universidad Complutense de Madrid and Universidade Lusíada - Universidad Complutense de Madrid (2018)
- Cooperate for exchange of students and/or staff in the context of the Erasmus+ programme; - Erasmus subject area: Criminology.